The Concentration of 25-Hydroxy Vitamin D in Chronic Liver Disease and its’ Correlation with Severity (Bangladesh Medical Journal, 2021)
Chronic Liver Disease (CLD) is a common disease all over the world and the major biological factors are Hepatitis B virus (HBV) and Hepatitis C virus (HCV) in Bangladesh and Alcoholic liver disease in the western world. Life expectancy of CLD patient is increasing now a days by available modern treatment; but the long term complications are now evident. Hepatic osteodystrophy is one of the most common complication which is associated with vitamin D deficiency. Vitamin D undergoes hepatic 25-hydroxylation, but as the hepatic parenchyma is jeopardized so the metabolic activation of this vitamin is impaired. The aim of the study was to measure the concentration of 25-hydroxy vitamin D 25(OH) D in CLD patient in different etiology and to find out the relationship of level of 25(OH) D in different stages of the disease according to Child-Pugh classification. This cross sectional study was carried out in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period of April 2015 to March 2016. Patients attending the Gastroenterology Department with cirrhosis of liver and who fulfilled the inclusion criteria were initially enrolled for the study. Study objectives were explained and informed consent was taken from patients prior to record their clinical history, examination findings and initial investigation reports in the standard data sheet. The diagnosis of liver cirrhosis was made by combination of clinical features, blood profile and trans abdominal ultrasonography (T. USG). Endoscopy of the upper GIT was also done to see the presence of oesophageal or gastric varices which is a sign of increase portal pressure. Stages of CLD were assessed by Child-Pugh scoring system and level of 25(OH) D was measured from blood with the help of the Department of Bio-chemistry. Data was collected using a structured data sheet and analyzed by SPSS. Out of 85 patients, male-female ratio was 3:1 and mean age was 53.0 ± 10.7 year within the range of 25-70 years. Most of the patients had acites 92.9% and anorexia 90.6%; where four-fifth patients had weight loss and more than one third had Jaundice. Nearly half of the patients had abdominal pain and 42.4% had melaena. Four-fifth patients had history of blood transfusion and most of them had H/O hospitalization 94.8%, anaemia (97.6%) and Splenomegaly 92.9%. More than half (52.9%) of patients had bone pain; where jaundice 61.2% and Leukonychia 61.2% were detected in equal number of patients. Mean  vitamin 25(OH) D was 16.29 ± 7.96 in 69 HBV patients and 20.14 ± 9.76 in 16 HCV patients. In this study, 28.2% patients were in child Pugh A, 36.4% in child Pugh B and 32.9% in child Pugh C stages. Mean  vitamin 25(OH) D were 27.12 ± 6.11, 15.97 ± 5.40 and 9.57 ± 1.I5 in Child-pugh A, Child-pugh B and Child-pugh C stages respectively. Mean vitamin 25(OH) D was observed at decreased level as the changes of stage from lower to higher. Vitamin D deficiency was highly prevalent in patients with CLD and inversely correlated with disease severity. In the case of chronic liver diseases, vitamin D seems to modulate the innate and adaptive immune system, which explains the association. This study suggest that these parameters may improve with vitamin D supplementation. Monitoring of S. 25(OH) D is reasonable in CLD patient.Bangladesh Med J. 2020 Sept; 49(3) : 35-42